Tanshinone I regulates autophagic signaling via the activation of AMP-activated protein kinase in cancer cells. Issue 6 (July 2020) - Zheng, Lihua; Zhang, Ying; Liu, Guijian; Cheng, Shi; Zhang, Ge; An, Cheng; Sun, Shipeng; Wang, Jian; Pang, Bo; Li, Shanhu
Abstract : Tanshinone I, one of the components of Salvia miltiorrhiza Bunge, exhibits anti-tumor ability and induces autophagy. But the mechanisms are not fully understood. This study aims to investigate whether AMP-activated protein kinase dependent pathway is involved in the autophagic signaling regulation and its relationship with tumor suppression. Breast cancer cells (MDA-MB-231, MCF-7) and hepatocellular carcinoma cells (HepG2) were treated with Tanshinone I or vehicle. Acridine orange dyeing and transmission electron microscopy were employed to evaluate autophagic cells. MTT and Cell Counting Kit-8 assays were used to detect the effect of Tanshinone I combined with autophagy inhibitors on cell proliferation. Western blot was used to detect the expression levels of Beclin1 and LC3-I/II, as well as the phosphorylation of AMPKα and ULK1. Our results showed that Tanshinone I suppressed proliferation of HepG2, MDA-MB-231 and MCF-7 cancer cell lines. LC3-II and P62 were induced by Tanshinone I in all three cancer cell lines. But autophagic flux analysis showed that Tanshinone I treatment induced autophagy only in MDA-MB-231, which was also proved by transmission electron microscopy. Tanshinone I upregulated the phosphorylation of AMPKα and its downstream ULK1. AMP-activated protein kinase inhibitor compound C attenuated Beclin 1 and LC3-II expression induced by Tanshinone I in HepG2. In MDA-MB-231, compound C surprisingly induced LC3-II upregulation which is independent of AMPKα activation. Under this circumstance, treatment of Tanshinone I combined with compound C significantly inhibited MDA-MB-231 proliferation, compared with Tanshinone I treatment alone. This study demonstrates that Tanshinone I could induce cancer cell death and regulate autophagy signaling in breast cancer and hepatic carcinoma cells. Activation of AMPKα was found to be involved in autophagic signaling regulation by Tanshinone I.